Physicochemical properties and antioxidant activities of jujubes (Ziziphus jujuba Mill.): effect of blackening process on different cultivars. Issue 1 (31st December 2022) - Song, Yaru; Chen, Chang; Wang, Fangzhou; Zhang, Yanlei; Pan, Zhongli; Zhang, Rentang
ABSTRACT: This study aimed to quantitatively assess the physicochemical properties and antioxidant activities of seven jujube cultivars (NYDZ, MZ, TZ, HZ, HTDZ, GTZ, and JSXZ) before and after the blackening process and to select the most suitable cultivar for blackening. Red jujubes were blackened by aging at high temperature (75°C) and humidity (80%) conditions for 6 days. The contents of soluble solids, total phenolics, total flavonoids, polysaccharides, cyclic adenosine monophosphate, 5-hydroxymethylfurfural, and antioxidant activities were analyzed using the spectrophotometric method and high-performance liquid chromatography (HPLC). Results showed that the antioxidant activities of all cultivars were significantly enhanced ( p <  .05) and the contents of selected bioactive compounds in all cultivars increased after blackening, indicating that blackened jujube had higher nutritional value than red jujube. Correlation analysis showed that the total phenolic compounds were the primary source of jujube antioxidant activities. The heat map showed that HTDZ could be selected as the most suitable cultivar for future production of blackened jujube. Red jujube cultivar with high total phenolic content was the best choice for blackening.